2011
DOI: 10.1007/s12011-011-9003-3
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Modulates Superoxide Dismutase, Uric Acid-Independent FRAP and Zinc in Blood of Adult Epileptic Patients

Abstract: We aimed to evaluate changes in antioxidant status in blood during valproate (VPA) monotherapy of adult patients with epilepsy. Antioxidant enzymes [plasma superoxide dismutase (pSOD), erythrocyte superoxide dismutase (eSOD)] and non-enzymatic indices [concentration of trace elements in serum: selenium, copper, zinc (sZn) and uric acid (UA), as well as the ferric reducing ability of plasma (FRAP) and UA-independent FRAP (UAiFRAP)] were evaluated in 21 adult patients with epilepsy and 21 healthy controls. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Therefore, administration of VPA induced suppressing activity on the immune system and antioxidant enzymes that may contribute to the development of organ toxicity and dysfunction (34). Płonka-Półtorak et al (35) found higher SOD activities in plasma and erythrocyte of patients treated with VPA. Whereas, Vidya and Subramanian (36) found decreased activities of antioxidant enzymes such as SOD, GPx and CAT in the liver and kidney tissues of rats treated with sodium valproate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, administration of VPA induced suppressing activity on the immune system and antioxidant enzymes that may contribute to the development of organ toxicity and dysfunction (34). Płonka-Półtorak et al (35) found higher SOD activities in plasma and erythrocyte of patients treated with VPA. Whereas, Vidya and Subramanian (36) found decreased activities of antioxidant enzymes such as SOD, GPx and CAT in the liver and kidney tissues of rats treated with sodium valproate.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant status of epileptic patients was modified by valproate monotherapy. The frequency of seizures and duration of VPA therapy were associated with changes of oxidative/antioxidative balance [224].…”
Section: Superoxide Dismutase/valproic Acidmentioning
confidence: 99%
“…An involvement of lipid peroxidation seems to be probable and the elevated activity of pSOD in some studies may be explained by this induction. Significant effects of duration of VPA therapy, activity of seizures and gender were found on Zn, pSOD, and erythrocyte SOD (eSOD) levels [4,9]. Also in prospective studies [18,19] were reported increased levels of eSOD in epileptic children after implementation of VPA treatment.…”
Section: Selenium Cooper Zincmentioning
confidence: 96%
“…20% [27]. In numerous studies, reduced carnitine levels were found during VPA therapy, especially with prolonged use and with high dosage levels [29]. The mechanism of this may include: 1) the formation of valproylcarnitine, 2) the reduction of tubular reabsorption of carnitine in the kidneys, 3) the inhibition of selected enzymes, which take part in biosynthesis of carnitine, 4) the inhibition of the membrane carnitine transporter and 5) the impairment of recycling of carnitine from long-chain acylcarnitines by the VPA-induced decrease of mitochondrial free Co-A level.…”
Section: Carnitine and Cellular Energymentioning
confidence: 99%
See 1 more Smart Citation